THE ANALYSIS OF MURDER IN MARY BURTON’S I’M WATCHING YOU THROUGH THE LENS OF CAWETI’S DETECTIVE FORMULA - Makawimbang, Prita D.; Mogea, Tini; Oroh, Elisabeth Z. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The research is mainly to find out cause of murder and how the murder happened. In Mary Burton’s novel entitled I’m Watching You. In conduction her research, the writer uses qualitative research since the data collected are in form of words not number. In analyzing the data, the writer applies detective formula as stated by John G. Cawelti. As the result of this research it found that murder can be revealed in the story I’m Watching You. The murder began from someone that call him self as The Guardian, and he want to protect his niece Lindsay, by kill someone who harms Lindsay. And in the and of the story, the murder can be revealed. And everyone know who The Guardian is, and why the murder happened.